Ullmann homocoupling of arenediazonium salts in a deep eutectic solvent. Synthetic and mechanistic aspects. Issue 41 (20th September 2022) - Ghigo, Giovanni; Bonomo, Matteo; Antenucci, Achille; Damin, Alessandro; Dughera, Stefano
Abstract : DES is exploited as a solvent media in Ullmann homocoupling of arenediazonium salts. Computational study supported by Raman spectroscopy is presented, aiming to elucidate the reaction mechanism. Abstract : A deep eutectic solvent (DES) based on glycerol and KF is successfully exploited as a solvent medium in Ullmann homocoupling of arenediazonium salts. The reactions were carried out in mild conditions and target products were obtained in fairly good yields. A computational study is presented aiming to understand the reaction mechanism and Raman spectroscopy is employed as an experimental tool to support it.